Facial Diplegia as an Initial Presentation of Guillain-Barré Syndrome - Aravind Surya Maddali; Karri Vijaya Phani Vardhan Reddy; Suganya Kavi; Tumbanatham Apikkatla (Journal of Clinical and Diagnostic Research, 2023)
Guillain-Barré Syndrome (GBS) is an acquired immune mediated inflammatory and demyelinating disorder of the peripheral nervous system. This case report is about a 30-year-old female who presented with unilateral facial palsy which progressed to bilateral facial nerve palsy without motor weakness of limbs. Cerebrospinal Fluid (CSF) analysis showed albuminocytological disassociation and Nerve Conduction Studies (NCS) of face showed decreased conduction velocity of nasalis and orbicularis oculi nerves. The patient was treated with intravenous immunoglobulin (0.4 g/kg/day) for five days and showed complete recovery. The present case is reported due to its rarity in presentation i.e. bilateral facial nerve palsy in the initial days of presentation.